The Qur’anic Spiritual Value of the “Pé-sapéyan Pappa” Social Learning to Improve the Madurese Migrants’ Quality Life - Hadi, Saiful (Ulumuna, 2023)
This study aims to examine pé-sapéyan pappa tradition amongst the Madurese migrants. It explores the Qur’anic spiritual values embedded in this tradition. The data were gained through observation to the informents’ life and interviews with them regarding their reasons for migration and the form of social learning that arises from such migration. The selected informants are migrants from Talango Island and Ghili Genting who live in several big cities, such as Jakarta, Jogjakarta, Surabaya, and Malang. This study shows that pé-sapéyan pappa can change the Madurese migrants’ mindset, deepening their knowledge and experience in managing businesses to improve their quality of life according to shari'a guidelines. The Qur’an enjoins Muslims to seek a sustainable life to suport a better spiritual life. Most migrants established a small and medium entrepreneurship to generate more income. The tradition, which was originated from the migrants’ hometown, help create a model of social learning in the host city, from which the migrants learn how to deal with the new situation and settle challenges.